APLIKASI DATA CITRA SATELIT UNTUK SIMULASI HIDROGRAF SATUAN METODE NAKAYASU DI SUB DAS BARITO DAN SEKITARNYA PROPINSI KALIMANTAN SELATAN - Abdur Rahman; Akhmad Murjani (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2017)
This research aims to simulate the arrival time of flood from upstream to downstream by using watershed data characteristic as early anticipation step as the early warning in flood disaster management that happened in Regency of Banjar by using unit hydrograph. Data Analysis Methods used to determine the simulation of the arrival time of the flooding using the Nakayasu Unit Hydrograph method combined with the SRTM satellite image data application then integrated with the Geographic Information System (GIS) The results showed that the Martapura River Basin, Banyiur River Basin, and Jaranang River Basin occurred flow debit or surface runoff (Qp) of 7.095 m3/s. This is because Martapura River Basin, Banyiur River Basin, and Jaranang River Basin have long river characteristic of 19.46 km and wide watershed 86.97 km2. Assuming that therain is falling evenly in Martapura River Basin, Banyiur River Basin, and Jaranang River Basin, it can be simulated that flood peak (Tp) occurs after 2.20 hours and will reach downstream of the river (T0,3) after 2.75 hours.